Structural evaluation of textile machine monitoring system support frame using finite element method - Deni Kurnia; Alif Firizky; Nanang Roni Wibowo; Raka Pratindy (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2026)
The development of an Internet of Things (IoT)-based textile machine monitoring system requires a reliable and mechanically safe support structure. A key issue in current practice is the design of control and monitoring frameworks that rely only on previous models without adequate testing and validation. This study aims to evaluate the structural strength of the textile machine monitoring system support frame using a Finite Element Method (FEA) approach. The 3D frame model was designed using CAD software and analyzed numerically through static simulation with a loading scenario of 100–150 N on the upper part of the structure. The material used is mild steel with mechanical characteristics commonly used in industrial applications. The analysis includes evaluation of Von Mises stress, displacement, and safety factor. The simulation results show a maximum stress of 0.5582 MPa, a maximum displacement of 0.001842 mm, and a safety factor exceeding 12. These values ​​indicate that the designed structure has excellent resistance to static loads and can be categorized as safe for use in industrial environments. This study provides a strong foundation for the development of a reliable and sustainable textile machine monitoring system support structure.